2016
DOI: 10.1096/fj.201500111r
|View full text |Cite
|
Sign up to set email alerts
|

A precursor‐inducible zebrafish model of acute protoporphyria with hepatic protein aggregation and multiorganelle stress

Abstract: Protoporphyria is a metabolic disease that causes excess production of protoporphyrin IX (PP-IX), the final biosynthetic precursor to heme. Hepatic PP-IX accumulation may lead to end-stage liver disease. We tested the hypothesis that systemic administration of porphyrin precursors to zebrafish larvae results in protoporphyrin accumulation and a reproducible nongenetic porphyria model. Retro-orbital infusion of PP-IX or the iron chelator deferoxamine mesylate (DFO), with the first committed heme precursor α-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 60 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…Cytosolic (K8/K18) and nuclear (Lamin A/C, Lamin B1) IF proteins have been reported to be highly susceptible to porphyrin-mediated aggregation. 11,12,24,25 Indeed, DDC caused upregulation of both K8 and K18 in both control+DDC and β-catenin DsiRNA+DDC livers as previously described 4 (Fig. 6A, 6B, upper panel, and Fig.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Cytosolic (K8/K18) and nuclear (Lamin A/C, Lamin B1) IF proteins have been reported to be highly susceptible to porphyrin-mediated aggregation. 11,12,24,25 Indeed, DDC caused upregulation of both K8 and K18 in both control+DDC and β-catenin DsiRNA+DDC livers as previously described 4 (Fig. 6A, 6B, upper panel, and Fig.…”
Section: Resultssupporting
confidence: 80%
“…Given that recent studies have shown the unique role of porphyrins in causing protein aggregation, 11,12,24 we next analyzed the extent of protein aggregation after DDC. SDS-PAGE and Coomassie blue staining show changes in the protein banding pattern as a function of DDC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most sequences in NCBI database were predicted based on bioinformatic analysis. In bony fishes, only the sequence of zebrafish (danio rerio) [11] was cloned. Interestingly, similar to yeast homology, zebrafish ATG16L1 is lack of WD40-repeat domain but predicted ATG16L1 sequence of other bony fishes such as common carp (cyprinus carpio) not.…”
Section: Introductionmentioning
confidence: 99%